Information System Design Orifice Type Concentric Based On Fuzzy Logic - Asepta Surya Wardhana,; Septian Dwi Saputra,; Alfin Sahrin,; Astrie Kusuma Dewi,; Erna Utami, (International Journal of Integrated Engineering, 2025)
This study addresses the challenges in orifice bore design by developing automated software for precise calculations meeting field specifications. The research introduces Oricalc, a Delphi 7-based software that automates orifice bore sizing calculations previously performed manually using the AGA Report No.3 standard. The software implements fuzzy logic for parameter interpolation, replacing traditional table-based methods. Comparative testing between Oricalc, manual calculations, and MATLAB simulations demonstrated average error rates of -0.03646, 0.44, and 0.48. The software additionally provides functionalities for calculating Gross Heating Value (GHV), compressibility, standard flow rates, and real-time flow monitoring. Uncertainty analysis revealed that instrumentation/sensors contributed 99.43% of measurement uncertainty, with flow rate and mechanical factors contributing 0.56% and 0.0000002% respectively. The negligible mechanical uncertainty validates the high accuracy of Oricalc's orifice bore calculations, confirming its effectiveness for industrial applications.